2023
DOI: 10.1039/d2qi01895k
|View full text |Cite
|
Sign up to set email alerts
|

A rigid–flexible double-layer steric strategy promoting ethylene polymerization and copolymerization in alkane solvents

Abstract: In this study, a series of double-layer steric α-diimine nickel and palladium complexes containing bulky diarylmethyl moieties with remote 4-cycloalkyl and -phenyl substituents were designed and synthesized. The as-synthesized nickel...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…It is known that the ratio between the chain growth rate and the chain walking rate is responsible for the microstructure of the polyethylene materials in α‐diimine nickel/palladium catalyzed ethylene polymerization, which ultimately determines their mechanical properties. [ 13,16,20,39‐41 ] The mechanical properties of the resultant semi‐crystalline polyethylenes were evaluated by tensile testing (Figure 4, Table S1). The branched polyethylenes generated by Ni1 — 3 exhibited high stress at break values (12.0—33.1 MPa) and high strain at break values (392%—1150%), manifesting the typical features of thermoplastics.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the ratio between the chain growth rate and the chain walking rate is responsible for the microstructure of the polyethylene materials in α‐diimine nickel/palladium catalyzed ethylene polymerization, which ultimately determines their mechanical properties. [ 13,16,20,39‐41 ] The mechanical properties of the resultant semi‐crystalline polyethylenes were evaluated by tensile testing (Figure 4, Table S1). The branched polyethylenes generated by Ni1 — 3 exhibited high stress at break values (12.0—33.1 MPa) and high strain at break values (392%—1150%), manifesting the typical features of thermoplastics.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of the polar polyethylene produced is reduced by an order of magnitude compared with that of the polyethylene obtained in the homopolymerizations (Table ). It should be emphasized that the MA incorporation ratios in our current study are high (8.5–21.4 mol %), substantially exceeding those of the α-diimine palladium system under similar conditions. A higher concentration of methyl acrylate (MA) is beneficial for obtaining higher insertion ratios (Table ). The Pd catalyst in this system demonstrates an exceptional ability to insert MA, resulting in an increased density of polar functional groups in the resultant polyethylene.…”
Section: Resultsmentioning
confidence: 67%
“…[25][26][27] Chen, Dai and their co-workers observed that the bulky ortho N-aryl substituents on α-diimine ligands enable the Pd(II) catalysts to yield PE with apparently higher molecular weight (level of 1000 kg/mol) and significantly lower branching density (6-26/1000 C). [28][29][30][31][32][33][34] The significantly lower branching density and higher molecular weight resulting in the semi-crystalline structure dramatically improves the mechanical properties of polymer materials. The Harth group introduced the m-xylyl substituents to the α-diimine Pd(II) complexes, in which the catalyzed living ethylene polymerization was observed.…”
Section: Introductionmentioning
confidence: 99%
“… 24 In order to generate the various branched PEs with the α‐diimine catalytic system, the ligands were always introduced with different hindrance 25–27 . Chen, Dai and their co‐workers observed that the bulky ortho N‐aryl substituents on α ‐diimine ligands enable the Pd(II) catalysts to yield PE with apparently higher molecular weight (level of 1000 kg/mol) and significantly lower branching density (6–26/1000 C) 28–34 . The significantly lower branching density and higher molecular weight resulting in the semi‐crystalline structure dramatically improves the mechanical properties of polymer materials.…”
Section: Introductionmentioning
confidence: 99%